Study of histopathological pattern of endometrium in abnormal uterine bleeding and its management - Singh, Alpana; Ramana Bai, P. V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Abnormal uterine bleeding is one of the most common and challenging problems presenting as an enigma to the gynecologist regardless of the age of the women. Histopathological evaluation of endometrium plays a significant and pivotal role in the diagnosis and management of endometrial causes of Abnormal Uterine Bleeding. The main aim was to study the frequency of different histopathological patterns of endometrium in patients with abnormal uterine bleeding across different age groups, know the endometrial causes of abnormal uterine bleeding and its managements. Methods: This study was conducted on 300 patients from March 2014 to February 2015 in the department of Obstetrics and Gynaecology in a reputed teaching hospital and research centre in South India. Demographic indices were collected and recorded. Endometrial samples were sent for histopathological examinations and different endometrial patterns were noted. Results: Abnormal Uterine Bleeding (AUB) presented mostly in the 41-50 years age spectrum (48.6%) and most of the patients were multipara. The main presenting complaint among our patients was menorrhagia (42%) followed by polymenorrhagia (15%), menometrorrhagia (10.6%) ,continuous vaginal bleeding (9.6%), Polymenorrhea (9.3%), postmenopausal bleeding (8.6%) and metrorrhagia (4.6%).The commonest histopathological pattern in abnormal uterine bleeding was normal physiological phases of menstrual cycle - proliferative and secretary endometrium (37% and 30% respectively). Endometrial hyperplasia was the most common endometrial pathology observed (22.6%). Conclusions: Endometrial evaluation in abnormal uterine bleeding in different age groups helps in the management, especially in the perimenopausal and postmenopausal age groups to rule out premalignant conditions and malignancy.